Innovation In Strategic Management And Its Impact On Business, Analysis And Risk Management In The Context Of Business Strategy - Fajar Pandu Nugroho; Gina Irena; Abdurojak Abdurojak; Nungky Nadya Madona; Hadi Supratikta (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
Innovation in strategic management plays a key role in business success in an increasingly competitive environment. This article aims to analyze how the application of innovation in strategic management impacts business analysis and risk management within the context of business strategy. Using a descriptive qualitative approach, this study explores various innovative models and practices adopted by companies to enhance competitiveness and the effectiveness of business strategies. The research also discusses how innovation not only affects long-term planning but also plays a significant role in managing risks arising from rapid market changes. Findings from this study show that innovation in strategic management helps companies formulate more adaptive and responsive strategies to both external and internal dynamics, thereby minimizing potential risks. Furthermore, the article highlights the importance of integrating comprehensive business analysis with the implementation of innovative strategies to optimize better business decisions. Therefore, the results of this study are expected to provide insights for practitioners and academics in formulating more resilient and sustainable business strategies.